DEVELOPMENT OF AN INNOVATIVE DEVICE FOR THE QUANTITATIVE AND QUALITATIVE ASSESSMENT OF MICROBIAL CONTAMINATION LEVELS IN THE AIR ENVIRONMENT OF LIVESTOCK FACILITIES AND VETERINARY SURVEILLANCE SITES - А. Alimov; Z. Aitpaeva; S. Sarimbekova; S. Junisbayeva; A. Koygeldinova; G. Aliyeva; N. Yedil (Animal Health and Biosafety, 2026)
The article presents the development of an innovative device designed for the quantitative and qualitative assessment of microbial contamination levels in the air environment of livestock facilities and veterinary surveillance sites. Microbial contamination of the air at veterinary-controlled facilities is one of the key factors affecting the health, productivity, and reproductive performance of farm animals and poultry. In this regard, the development of effective methods for the rapid monitoring of the aeromicrobiological state of livestock and poultry housing is of particular relevance. Existing air quality monitoring methods have a number of limitations, including labor intensity, lengthy analysis time, and insufficient sensitivity, which necessitates the creation of more advanced technical solutions. This study presents the development of an innovative device for the quantitative and qualitative assessment of microbial air contamination. The device is based on the principle of aspirational sampling followed by the capture of microorganisms in a liquid medium. A distinctive design feature is the presence of a spherical mixing nozzle that ensures intensive mixing of the air stream with the capturing liquid, increases the contact time between phases, and stabilizes sampling parameters. The use of a bellows pump enables sampling for 2 - 3 minutes without the risk of liquid entering the nozzle orifice, thereby improving the reliability and reproducibility of the results. The developed device is characterized by a simple design, ease of manufacture, and operational convenience, making it suitable for use in various types of livestock facilities, including dairy barns, maternity units, and calf housing. Experimental validation demonstrated high efficiency in capturing bacterial and viral aerosols over a wide range of concentrations. A comparative analysis with traditional microbiological monitoring methods (Koch’s method, Matusevich’s method, and the use of the Krotov apparatus) showed the advantages of the proposed device in terms of sensitivity, accuracy, and efficiency. The obtained results confirm the prospects for implementing the developed device in veterinary surveillance practice to enhance the effectiveness of sanitary-hygienic control and ensure the biological safety of livestock enterprises.